Advancement of E-Book Through Automation System in Department of Islamic Education (STAI) Miftahul Ula Nganjuk - Barid Nizarudin Wajdi, Muh; Halim, Paisal; Badruddin, Syamsiah; ., Hartono; A. Abdullah, Hasim; Ikhsan Setiawan, Muhammad; Novita Sari, Ifit; Puji Nali Brata, Diah; Simarmata, Janner (International Journal of Engineering and Technology, 2018)
Improving quality of learning related to the management of supporting facilities in the learning process cannot be separated from the library facilities implemented by the librarian. It is essential to ensure that the learning activities can be done well. Therefore the librarian is asked to design a system called Library Automation. Instructional design in E-Book development methodology with this library Automation system uses library to study and field study using observation and interview. This system is made to accelerate the typical daily activities. The application of automation gives a great advantage; the students can be able to find the information quickly. Furthermore, this automation system is already based on Online. The existence of the e-book gives the significant benefits in STAI Miftahul Ula Nganjuk. In expanding perusing interest, the presence of the digital book can likewise enhance the administrations institutionally, takes care of its requests advancement, improves the execution, and keeps up a realness of an archive. The understudies are exceptionally happy with this framework. They generally get the data about the books despite the fact that they are not on grounds condition.Â Â